2022
DOI: 10.1007/s11042-022-14216-w
|View full text |Cite
|
Sign up to set email alerts
|

An efficient hybrid stock trend prediction system during COVID-19 pandemic based on stacked-LSTM and news sentiment analysis

Abstract: The coronavirus is an irresistible virus that generally influences the respiratory framework. It has an effective impact on the global economy specifically, on the financial movement of stock markets. Recently, an accurate stock market prediction has been of great interest to investors. A sudden change in the stock movement due to COVID -19 appearance causes some problems for investors. From this point, we propose an efficient system that applies sentiment analysis of COVID-19 news and articles to extract the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The use of machine learning, deep learning, and reinforcement learning models for future stock price prediction has been the most popular approach of late [11][12][13][14][15][16][17][18][19][20][21][22][23]. Hybrid models are also proposed that utilize the algorithms and architectures of machine learning and deep learning and exploit the sentiments in the textual sources on the social web [24][25][26][27][28][29].…”
Section: Related Workmentioning
confidence: 99%
“…The use of machine learning, deep learning, and reinforcement learning models for future stock price prediction has been the most popular approach of late [11][12][13][14][15][16][17][18][19][20][21][22][23]. Hybrid models are also proposed that utilize the algorithms and architectures of machine learning and deep learning and exploit the sentiments in the textual sources on the social web [24][25][26][27][28][29].…”
Section: Related Workmentioning
confidence: 99%
“…Results indicated that combining sentimental information from both sources improved model accuracy. In [16] Sharaf, Hemdan, El-Sayed and El-Bhnasawy presented a survey of sentiment analysis and stock analysis, followed by the introduction of an efficient proposed system that combines sentiment analysis of social news and historical data analysis. The proposed system faced limitations during the Covid-19 period.…”
Section: Related Workmentioning
confidence: 99%
“…In (Sharaf et al 2022), news headlines pertaining to TSLA, AMZ, and GOOG stock were considered to obtain good-quality data to reduce spam tweets through feature selection methods. Sentiment analysis was also used for polarity detection and historical data mining, for which DL algorithms were used.…”
Section: Comprehensive Summary Of Theoretical Basismentioning
confidence: 99%